2021
DOI: 10.1080/2331205x.2021.1966179
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Pakistan: Challenges and priorities

Abstract: has big health issues which affect worldwide beyond their borders, race, and ethnicity. All the countries faced this pandemic challenge but most of the underdeveloped countries are facing more dangerous situations due to limited financial and health infrastructure to respond against it. Overall, more than 100 million people are affected by the Novel Virus which results in 2.15 million people dying within a small interval of time. The current pandemic has brought unpredicted challenges to societies and also thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Studies have demonstrated that nancial and logistics challenges have also been observed for many of the departments and sectors engaged in COIVD-19 response (18) (19). Most of the organizations were not having dedicated funds to support day to day COVID-19 response activities (including testing, surge staff and deployment, quarantine, door to door vaccination etc) (20). For immediate nature of tasks, NCOC has coordinated with national and international developmental partners for logistic support from centralized location (11).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that nancial and logistics challenges have also been observed for many of the departments and sectors engaged in COIVD-19 response (18) (19). Most of the organizations were not having dedicated funds to support day to day COVID-19 response activities (including testing, surge staff and deployment, quarantine, door to door vaccination etc) (20). For immediate nature of tasks, NCOC has coordinated with national and international developmental partners for logistic support from centralized location (11).…”
Section: Discussionmentioning
confidence: 99%
“…Although Pakistan's economy per-formed well amid the Covid-19 outbreak resulting in a 3.94 percent economic growth rate during the fiscal year (20) But to keep such indicators persistent would remain an uphill task. Hence, it is inevitable that the policymakers and top brass management of the country should keep a comprehensive plan to avoid any further burden on the already frail health system of the country (21). Further, as no country can be insulated by the virus, therefore the world may need to come up with a global strategy to combat the pandemic and the threats posed by it.…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan also faces severe challenges to beat COVID-19 because of bad governance system and weak financial position [ 3 ]. One of the most powerful tools for solving such a critical condition is the selection of suitable policy measures [ 36 ].…”
Section: Literature Reviewmentioning
confidence: 99%